Analyzing Systemic Risk in the Chinese Banking System - Qiubin Huang; Jakob de Haan; Bert Scholtens (Center for Economic Studies and ifo Institute (CESifo), 2015)
We examine systemic risk in the Chinese banking system by estimating the conditional value at risk (CoVaR), the marginal expected shortfall (MES), the systemic impact index (SII) and the vulnerability index (VI) for 16 listed banks in China. Although these measures show different patterns, our results suggest that systemic risk in the Chinese banking system decreased after the financial crisis, but started rising in 2014. Compared to the banking systems of Korea and the US, we find that Chinese banks are at greater risk according to the CoVaR, the SII and the VI approaches, but have the lowest MES.
Keywords: G21; G28; G14; 330; systemic risk; Chinese banking system; CoVaR; capital shortfall